"Circassian" narratives in modern politics of memory in Georgia (2011–2021) - M. V. Kirchanov (Кавказология, 2025)
This study analyzes the Circassian dimension in the modern Georgian politics of memory. The author analyzes the main vectors and trajectories of the development of Circassian narratives in the modern memorial canon of Georgia. The novelty of the study lies in the analysis of the practices and strategies used by Georgian intellectuals within the framework of the functioning of Circassian narratives in the modern memorial canon of Georgia as an element of the politics of memory. The article analyzes 1) the role of political elites and the media in the formation of Circassian narratives in the politics of memory, 2) the features of the performative turn in the historical policy of promoting Circassian images, 3) the role of Circassian narratives in the “wars of memory”. This article shows both the merging and conflict potential of the Circassian dimension in Georgian historical politics. The author analyzes the roles of state authorities and the media as the key participants in the policy of memory and formatters of the memorial canon. It is assumed that the Circassian narratives in the modern memorial canon are predominantly symbolic for solving internal political problems, since external factors minimized the real influence of Georgia in the region. The results of the study show that the Circassian narratives in the Georgian politics of memory became an element of the ideological legitimization of the elites and the promotion of the concept of Georgia’s special role in the Caucasus, as well as the formation of alternative versions of memory to the perception of Circassian images in the Russian historical imagination.